Challenging perceptions in primary education : exploring issues in practice - Sangster, Margaret (Bloomsbury Academic, 2015)
"What are the beliefs that influence your professional practice? Have you ever thought about why you make the decisions you make as a teacher? What influences your teaching style? Beyond the technical skills and knowledge aspects of education, teachers and student teachers face questions which challenge their beliefs and approaches to their teaching and learning. This book contains a series of short articles which not only offer guidance on key topics but encourage the reader to engage in reflecting on their own practice. Questions explored include: - Is learning through practical work worth the effort? - What can we learn from comparisons with education in other countries? - Is there a smarter way to use digital imagery in your teaching? - What's the point of theory? Isn't teaching just a craft?"--